Differences in Stock Price Sensitivity to Accounting Information : Implications for Creative Accounting - Kameshwar Rao, M. V. S.; Lubza Nihar, K. (Indian Journal of Finance, 2016)
Purpose/Objective: This paper is an attempt to re-visit the concept of value relevance of accounting information to draw implications for creative accounting. It explores the hypothesis that value relevance, of various accounting variables, varies depending upon the business sector to which the firm belongs. Design/Methodology/Approach: This paper verified the above objective in the Indian context for firms in the BSE SENSEX using annual data for the period from 2000-2013 and generalised least squares regressions in the log-log form, with stock prices as dependent variables and the contemporaneous BSE SENSEX as the control variable. Book value of equity, revenue, profits after tax, and dividend were the chosen accounting items whose value relevance was examined (independent variables). Sector wise, cross sectional regression analysis was performed. To examine the significance of each of the independent variables on the stock price, univariate regressions were undertaken. Findings: The regression results indicated that the value relevance of the chosen accounting variables varied depending on the business sector. While profits after tax significantly influenced the stocks of all chosen sectors except for automobile ; additionally, revenues in the case of IT and FMCG and book value of equity in the banking sector influenced the prices of their stock prices. In the case of automobiles, ’revenues’ is the only significant explanatory variable of stock price. Originality/Value : This paper adds a new dimension to the literature of creative accounting. It suggests that the choice of the creative accounting variable might depend on the business sector to which the firm belongs to create the desired positive impact on the stock price.